Comparative Analysis of Management Competencies’ Effect on Civil Service Performance in Addis Ababa and Adama City Administrations, Ethiopia - Moti, Daba (African Journal of Leadership and Development, 2023)
In civil service institutions, civil service performance is a topic of wide interest. Managers who possess high levels of management competencies are more productive in providing civil services to the citizens. However, civil services are characterized poorly because of mal-practicing of management competencies. The main objective of this study was to analyze and compare management competencies’ effect on civil service performance. The study employed both quantitative and qualitative approaches using data collection tools that include structured and un-structured questionnaire, focused group discussions and key informant interviews. The SPSS statistic was used for the descriptive and inferential analysis. The findings indicate that the determinant factors contribute to the average level of civil service performance of the two study areas. However, the results describe small differences in the overall performance of the two study areas. The performance in the responses and mean values of the Addis Ababa City Administration is relatively better than that of Adama City Administration of Oromia. Although the implementation process has brought acceptable results, it is not free from some challenges. Lack of development of long-term strategies; lack of encouraging and recognizing creative ideas of employees; lack of stakeholders and partners involvement in the decision-making process; lack of continuous learning and self-development; lack of maximizing resource value efficiency against strategic priorities and lack of using modern technology are the major limitations pinpointed. The institutions should strengthen the efficiency and effectiveness of contributing factors of competency development to improve institutional competitiveness and its performance in today’s work environment.